Effect of sowing date and plant density on bolting of four sugar beet (Beta vulgaris L.) varieties - Entessar Al-Jbawi; Waeel Sabsabi; Gharibo Gharibo; Abd El-Muhsien Al-Sayed Omar (International Journal of Environment, 2015)
This experiment was conducted in Homs Agricultural Research Station, Homs, Syria during 2007/2008 and 2008/2009 seasons to study the effect of sowing date and plant density on bolting for four sugar beet varieties, tow are monogerm varieties i.e. Parade and Etna, while the other are multigerm varieties i.e. Nadir and Mammoth. Three sowing dates were applied, began from 15/9 to 15/10, the interval between the sowing dates was 15 days. Three plant densities were executed (133 000, 100 000 and 80 000 plantha-1). Split plot design was used with three replicates. The combined analysis exhibited the significant effect of varieties (V), sowing dates (S), and plant densities (D) on all types of bolting (Early, medium, late and total). Least significant test (L.S.D 0.05) clarified that early autumn sowing (15/9 and 1/10) increased total bolting percent 74.86 and 44.88 % respectively, as compared with date (15/10) 15.57% (control). The plant density (133 000 plant ha-1) decreased total bolting percent 43.56% as compared with the other plant densities (80 000 and 100 000 plant ha-1) 46.35 and 45.40% respectively. The results showed that the monogerm varieties were superior and more resistant to bolting as compared with the multigerm ones. DOI: http://dx.doi.org/10.3126/ije.v4i2.12647 International Journal of Environment Vol.4(2) 2015: 256-270